The compendium of trade & exchange circulars 1989 - Central Bank of Nigeria; Trade & Exchange Department of CBN (Abuja, Nigeria Central Bank of Nigeria, 2002)
This book is a collection different circulars on trade and exchange authorized by the CBN.
volume iv
mf 25/01/2019
Arch
Keywords: Abuja, Nigeria